Enhancing the value of public vintage seismic data in the Italian offshore. (28th December 2018) - Diviacco, Paolo; Firetto Carlino, Marco; Busato, Alessandro
Abstract: Vintage geophysical data represent a huge heritage for the whole scientific community (Sopher, 2018; Schaming et al ., 2017; Diviacco et al ., 2015) because, despite the antiquated acquisition methods and processing tools, they are generally characterized by high penetration and wide regional extension. Nowadays such large‐scale projects are in fact very difficult to take place, considering environmental, geopolitical, and funding issues. In addition, reprocessing vintage seismic profiles using up‐to‐date software and tools, it is now possible to further increase their original signal‐to‐noise ratio. Italian offshore areas have been widely investigated by a dense network of multichannel seismic reflection profiles, acquired by the Italian Authorities in the years 1960, 1970, and 1980 of the last century in the perspective of mineral prospecting. This asset of data has been recovered, reprocessed, and made accessible within a demanding project undertaken by Istituto Nazionale di Oceanografia e di Geofisica Sperimentale (OGS). The present work aims at describing the data recovery and reprocessing methodologies applied to enhance the quality of these vintage multichannel‐seismic reflection profiles, and at detailing how to access this huge dataset, that have been made compliant with the FAIR principles (Findable, Accessible, Interoperable, Reusable) and available through the OGS‐SNAP data management web portal. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttps://doi.org/10.6092/SNAP.cbbba251c17b55c737836768c8737589 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .